(untitled) (The Nepalese Management Review, 2024)
Work-life Balance is the balance between family life and job life of an individual. The work-life balance is an individual. The work-life balance is an important dimension which can support to increase job satisfaction. The purpose of this study was to examine the work-life balance among commercial banking employees in Pokhara. Non-managerial level commercial banking employees were the respondents of the study. Convenience sampling technique was used to determine the number of respondents. Data were collected from 209 (102 male and 107 female) respondents through self structured questionnaires. This study was conducted to fulfill the gap and to cover a broad area of WLB. Work Family conflict (WFC) and Family work Conflict FWC were studied to know WLB. Statistical tools, mean, standard deviation, Independent sample t-test, one-way ANOVA. The findings of the study indicated that both WFC and FWC of WLB dimension influence on the work-life balance of commercial banking employees. The commercial banking employees Human resource management team should maintain work-life balance among employees for better and sustainable performance. The future researchers need to research study with covering work life balance on other nature banking institution employees and if commercial banking employees then on managerial employees.